Chemical characterization and in vitro cyto- and genotoxicity of ‘legal high’ products containing Kratom (Mitragyna speciosa) - Oliveira, Ana Sofia (2017)
Kratom is a popular ‘legal high’ mainly constituted by alkaloids extracted from the Mitragyna speciosa plant with mitragynine (MG) as the dominant active substance. The increasing use of Kratom for recreational purposes has alerted risk assessment bodies of the lack of information on the real composition and its potential health risks. The present study aimed to determine and compare the MG composition of 13 commercial products of Kratom sold online and in “smartshops”, by gas chromatography–mass spectrometry. For the first time, the cytotoxicity induced by pure MG and Kratom, extracts was evaluated in in vitro models of human intestinal (Caco-2) and neuronal (SH-SY5Y) cells after 6 and 24 h. Genotoxicity was also evaluated in intestinal Caco-2 cells following 24 h of exposure to subtoxic concentrations using the comet assay. The obtained results revealed an inconsistency between the information (‘power’) provided in labels and the MG content. Cytotoxicity tests revealed a concentration-dependent decrease in cell viability in both cellular models, with the SH-SY5Y cells being more sensitive to the Kratom extracts. The resin and the ‘powered extracts’ were the most cytotoxic samples, with IC50 values significantly lower than the leaf extracts and pure MG (P < 0.0001 vs. leaf extracts and MG). In addition, significant DNA damage was observed in Caco-2 cells exposed to these extracts but not to pure MG, which suggests that other substances present in the extracts or interactions involving Kratom components might be responsible for the observed effects.